Strengthening of prestressed concrete beams using combined externally bonded and prestressed near surface mounted technique / M. Obaydullah - M. , Obaydullah (2021)
Prestressed concrete beams are now widely used in the construction field. However, there is a lack of studies on the strengthening of prestressed beams. Externally bonded reinforcement (EBR) and near surface mounted (NSM) strengthening have been used to a certain extent to strengthen prestressed beams. However, EBR is prone to premature debonding failure, while NSM reduces but does not completely eliminate premature debonding. Prestressed NSM (PNSM) strengthening is new area of research. In this research work the possibility of using both steel strands and CFRP bars with PNSM strengthening is investigated. A new strengthening technique, the combined EBR with prestressed NSM (CEBPNSM) technique is also proposed in this research work to overcome the limitations of EBR and NSM. In this study, a total of thirty two prestressed beams were strengthened in order to investigate the structural performance of steel strands and CFRP bars as PNSM reinforcement, as well as the performance of the newly proposed CEBPNSM technique. The beam specimens were divided into six groups according to the type of strengthening conducted on the beams. The first group was strengthened with NSM CFRP bars. The second group was strengthened with NSM steel strands. The third group was strengthened with NSM CFRP bars and EBR CFRP sheet. The fourth group was strengthened with NSM steel strands and EBR CFRP sheet. The fifth group was strengthened with NSM CFRP bars and EBR CFRP plate. The sixth group was strengthened with NSM steel strands and EBR CFRP plate. The prestress levels in the PNSM and CEBPNSM strengthened beams were also varied from 30% to 70% of the tensile capacity of the NSM strengthening materials to study the effect on the prestressed beam. A numerical model was also developed using finite element modeling (FEM) to simulate the structural behavior of the strengthened beams and validate the experimental results. The results of this study showed that both steel strands and CFRP bars were effective as PNSM reinforcement, although steel strands displayed better ductility and serviceability. This study also found that the CEBPNSM strengthening technique improved the structural performance of the prestressed beam significantly more than other strengthening techniques. The ultimate capacity of the CEBPNSM strengthened beams increased by 67% to 81%, depending on variations in the strengthening materials and prestress levels. The serviceability, deflection, and failure mode of the CEBPNSM beams also improved considerably. Increasing the prestress level in the PNSM and CEBPNSM strengthened beams resulted in corresponding increases in flexural performance and load capacity, especially at the service stage. The highest level of prestress (70%) provided the greatest enhancement in flexural performance. The load deflection behavior and damage patterns generated by the FEM model were compared with the experimental results and found to be in good agreement.